Atrial Septal Aneurysm in Adult Patients of Therapeutic Hospital - O. V. Ryazantseva; N. I. Lenkova; O. D. Ostroumova; E. V. Shikh; S. M. Rykova (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To study detection of atrial septal aneurysm (ASA) by transthoracic echocardiography in patients of the older age group of the therapeutic hospital, as well as combinations with other structural disorders of the heart and blood vessels, as well as other signs of congenital connective tissue dysplasia (CCTD) of other localization.Material and methods. Identification of ASA as well as other signs of CCTD was performed in patients ≥40 years hospitalized due to exacerbation of therapeutic diseases (n=1119), which had transthoracic echocardiography.Results. ASA was found in 1.34% of patients (n=15). Undifferentiated connective tissue dysplasia was diagnosed in 14 (93.3%) ASA patients. Prolapse of mitral (60%), tricuspid (33.3%) or both atrio-ventricular valves of the heart (6.7%), patent foramen ovale (33.3%), rudimentary Eustachian valve (6.7%), additional ventricle chords (13.3%), Valsalva sinus dilation (6.7%) was found in ASA patients. 14 (93.3%) patients had electrocardiography signs of cardiac rhythm and conduction disorders. Chronic venous insufficiency (100%), disorders of the musculoskeletal system (100%), hiatal hernia (40%), anterior abdominal wall hernia (46.7%), nephroptosis (46.7%), kidney cysts (33.3%) intestinal diverticula and dolichosigma (26.7%), bronchiectasis (6.7%) were also found.Conclusion. ASA was found in 1.34% of patients in a therapeutic hospital ≥40 years. Clinically significant and prognostically unfavorable CCTDs were not found in ASA patients in this study. However, physicians should consider the possibility of the presence of other abnormalities of the heart and large vessels, as well as other systems and organs that can lead to fatal events, in these patients.